DOI: 10.31274/rtd-180814-5133
|View full text |Cite
|
Sign up to set email alerts
|

From chatting to confidence: a case study of the impact of online chatting on international teaching assistants' willingness to communicate, confidence level and fluency in oral communication

Abstract: Research question 3: Does the language experience of the chat actually transfer from the written mode into spoken language? Research question 4: Does chatting improve learners' fluency in oral communication? Statistical methods CHAPTER 4. RESULTS AND DISCUSSION 63 Impact of chat on willingness to communicate (WTC) 63 Impact of chat on state commimicative self-confidence. 66 Impact of chat on state anxiety 70 Impact of chat on state self-perceived competence Transfer of language experience from written to spoke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Further, replications with more and less anxious learners are also recommended. As already stated, the finding that learners are less anxious is an important one and merits further investigation because it suggests that text chat might break the ‘vicious circle’ of speaking anxiety and low speaking proficiency (Compton 2002: 25). While a likely explanation for the finding is that text chat places less time pressure on learners than voice chat, as the authors themselves suggest, there are a number of other possible explanations for the findings.…”
Section: The Original Studies and Suggested Approach To Replicationmentioning
confidence: 98%
See 1 more Smart Citation
“…Further, replications with more and less anxious learners are also recommended. As already stated, the finding that learners are less anxious is an important one and merits further investigation because it suggests that text chat might break the ‘vicious circle’ of speaking anxiety and low speaking proficiency (Compton 2002: 25). While a likely explanation for the finding is that text chat places less time pressure on learners than voice chat, as the authors themselves suggest, there are a number of other possible explanations for the findings.…”
Section: The Original Studies and Suggested Approach To Replicationmentioning
confidence: 98%
“…First, it focuses on a learner variable which has been found to be negatively associated with oral test performance, namely foreign language learning anxiety (Phillips 1992; Hewitt & Stephenson 2012). Second, it identifies a possible solution which may help break the ‘vicious circle’ of speaking anxiety and low speaking proficiency (Compton 2002: 25, cited in Satar & Ӧzdener 2008). At post-test, Satar & Ӧzdener (2008) found that learners who had completed tasks through the medium of text chat during their intervention had lower levels of anxiety than learners completing tasks through the medium of audio chat.…”
Section: Introductionmentioning
confidence: 99%
“…Most students agreed that the CMC tasks were a useful practice for future spoken conversations. It might be that this perceived growth boosted their self-confidence and sense of accomplishment, which helped in decreasing hesitation when speaking, thus breaking the vicious circle of helplessness as explained by Compton (2002).…”
Section: The Transfer From L2 Text Chat To Oral Task-based Performanc...mentioning
confidence: 99%
“…These studies have provided the field with evidence that CMC alters the traditional rules of classroom-based interaction thereby promoting increased participation and opportunities for L2 use among a wider range of students. This has resulted in further research which has investigated, for example, whether network-based CMC would facilitate the development of grammatical competence through the negotiation of meaning (Pellettieri, 2000) or whether the confidence building of text chatting would lead to an increase in spoken fluency (Compton, 2002). In spite of these beneficial opportunities computer-mediated interaction can provide in second language learning environments, analysis of CMC interaction in a range of contexts has identified social, linguistic, and technical factors which can limit the richness of interaction in a CMC environment.…”
Section: Cmc In the L2 Classroommentioning
confidence: 99%